Analysis of venom gland gene functions between adaptive radiations of Hawaiian Spiders - Simmons, Shania Carol Suzinn (East Carolina University)
The Hawaiian Tetragnatha spiders are a compelling model for studying adaptive radiation because of their rapid diversification into distinct ecological forms, including orb-weaving and ground-hunting species. This thesis investigates how evolutionary pressures have influenced functional gene expression in the venom glands of eight Tetragnatha species native to the Hawaiian Islands. The study examines whether ecological variation among species is reflected at the molecular level through comparative transcriptomic analysis and functional annotation using Gene Ontology (GO) terms. RNA was extracted and sequenced from venom glands, and the resulting data were used to identify GO terms associated with gene function, biological processes, and cellular localization. Functional annotations were performed using Blast2GO and InterProScan. Data were further analyzed and visualized through Principal Component Analysis (PCA), semantic scatterplots, tree maps, and word clouds. The findings reveal distinct differences in venom gland gene functions between orb-weaving and spiny-legged spiders. Ground-hunting species displayed greater diversity in molecular activities related to neurotoxicity, signal transduction, and enzymatic processes, which may support their active foraging strategies. These results demonstrate that ecological adaptation can drive not only changes in behavior and morphology but also divergence in gene expression patterns related to venom. This research links molecular data with ecological context and contributes to a broader understanding of how adaptive radiation shapes the evolution of functionally important traits in non-model organisms.
Keywords: Biology, Bioinformatics; Biology, General